Leaders’ learning orientation and the HCM-turn in call centres - Gnauer, Dorina (Academic Quarter | Akademisk kvarter, 2013)
Research on call centres is increasingly concerned with high levels of work intensification and unveils deep-seated contradictions in this new form of service organizations. The current debate opposes management interests in rationalization and technologies of efficiency and control to employee wellbeing and the quality of the customer service. Based on a single-case study, this paper advances a differentiated view of management focusing on the mediating role of operational management in striking a balance between structural requirements and people issues. Learning orientation is identified as a significant leadership quality that promotes reflexivity in the ongoing processes of interpretation and meaning creation enhancing the human dimension in the production of service. Learning orientation will be related to high-commitment management (HCM) as a way to reconcile the logics of efficiency and customization. Arguably, a learning orientation impacts not only at shop floor level, but also on the upper organization, through upward feedback, providing potentially valuable knowledge to the organizational strategic decision making.